First confirmed complete incubation of a flapper skate (Dipturus intermedius) egg in captivity. Issue 3 (19th June 2021) - Benjamins, Steven; Cole, Georgina; Naylor, Adam; Thorburn, James A.; Dodd, Jane
Abstract: An egg of the critically endangered flapper skate Dipturus intermedius was successfully incubated to hatching in captivity in what is believed to be a first for the species. Water conditions (temperature, salinity, flow rate) were recorded, with mean water temperatures ranging from a monthly mean of 8.3 ± 1.2 to 13.2 ± 0.3°C and salinity from a monthly mean of 30.5 ± 1.2 to 36.6 ± 2.3 ppt. Hatching occurred after 534 days, suggesting that flapper skate eggs take c . 5700 growing degree‐days to incubate to hatching. The egg's prolonged embryonic development raises concerns about flapper skate eggs' vulnerability to anthropogenic disturbance.